The Influence of The Reading Concept Mapping-Student Team Achievement Division (REMAP-STAD) Model on Students' Metacognitive Skills and Cognitive Learning Outcomes - Kusuma, Anindita SHM; Busyairi, Ahmad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
Metacognitive skills and cognitive learning outcomes are two competencies that students should have after learning is carried out. However, in reality, the increase in these two competencies has so far not been optimal. This research aims to determine the effect of the Reading Concept Mapping-Student Team Achievement Division (Remap-STAD) learning model on students' metacognitive skills and cognitive learning outcomes. This type of research is quasi-experimental with the One-group Pretest-Posttest Design. The instrument used in this research is in the form of essay questions. The technique for assessing metacognitive skills and student learning outcomes is carried out in an integrated manner. Hypothesis testing was carried out using statistical tests by comparing two means (pretest mean and posttest mean) using Paired Samples t-test analysis. The results of data analysis show that there is an influence of the Remap-STAD learning model on students' metacognitive skills and cognitive learning outcomes. Thus it can be concluded that the Remap-STAD learning model can be used as an alternative learning to improve metacognitive skills and student learning outcomes in higher education.